Effectiveness of Jin’s 3 Needles and INMAS Acupuncture in Reducing Low Back Pain - Puspitaningrum, Cynthia Ayu Dian; Purwanto; Widyastari, Sri (Jurnal Keterapian Fisik, 2025)
Background: Low back pain is one of the musculoskeletal disorders caused by poor body activity. Acupuncture for low back pain can stimulate the body to secrete endorphins which cause the body to become comfortable and relaxed, so that the degree of pain in the low back can be reduced. This study aims to compare the effect of Jin's 3 needles acupuncture therapy with Integrative Neuromuscular Acupoint System (INMAS) on changes in the degree of low back pain. Methods: This study used the two groups pre and post test design. The sample was 36 research subjects who met the inclusion and exclusion criteria and were selected using a simple random sampling technique, divided into 2 groups, namely the Jin's 3 needles group and the INMAS group. The data were analysed using the Wilcoxon test for changes within groups and the Mann–Whitney test for comparisons between groups. Results: The acupuncture therapy intervention of the Jin's 3 Needles method and the INMAS method is effective in reducing the degree of low back pain (p-value:<0.001). There is no significant difference between acupuncture therapy interventions Jin's 3 Needles method and INMAS in reducing the degree of low back pain (p value 0.769). Conclusion: There is an effect of acupuncture therapy Jin's 3 Needles and INMAS on changes in the degree of low back pain and there is no significant difference between the two interventions. Both interventions can be considered as non-pharmacological treatment options for lower back pain.